The periodontal effect of bleeding on probing and probing depth for molar bands and bondable buccal tubes - Rahman, M. Azizur; Hassan, Gazi Shamim; Sajedeen, Mahmood; Biswas, Ashis Kumar; Hasan, M. Kamrul; Rahman, Hassan Abeedur; Al Faruq, Abdullah (International Journal of Advances in Medicine, 2025)
Background: With rising life expectancy and esthetic awareness, more patients seek orthodontic treatment. This study shows molar bands cause more plaque retention, leading to higher bleeding on probing (BOP) and probing depth (PD) compared to bondable buccal tubes. Methods: This non-randomized control clinical trial was conducted at the department of orthodontics, Bangabandhu Sheikh Mujib medical university hospital (BSMMU), Dhaka from the period of December 2016 to August 2017. The test sample was 40 molar teeth of 10 orthodontic patients who were selected consecutively from patients selected for fixed orthodontic treatment in BSMMU. Results: The patients were aged 13-22 years [Mean (±SD) age=16.0±2.90 years]. The 20 molar teeth of the upper arch of selected patients were banded with molar bands (Group A). The 20 molar teeth of the lower arch of selected patients were bonded with bondable buccal tubes (Group B). The presence of BOP in molar bands at T1, T2 and T3 was 0 (0.0%), 2 (10%) and 4 (20%). The presence of BOP in bondable buccal tubes at T1, T2 and T3 was 0 (0.0%). There was a statistically significant increase was observed in the mean PD values for molar bands from T1 to T2 (p=0.001), from T2 to T3 (p=0.001), and from T1 to T3 (p=0.030). Conclusions: This study analyzed data over three and six months, finding that molar bands led to greater increases in BOP and PD than bondable buccal tubes, but long-term periodontal effects remain unclear.